Secado por lecho fluidizado de Zingiber officinale (jengibre o kión) - Del Aguila Tang, Hingler Djacmen (2015)
The Fluidized Bed Dryer Method is common in the industry to dehydrate foods with high humidity in granulated products with a temperature of 40 °C to 150 °C, passing a current flow in hot air with varied speed, in this method the conditions are fast in a transfer of mass and heat through a bed of particles. The objectives in this work were to obtain the drying parameters of Ginger or Kion (Zingiber Officinale) in a fluidized bed. The food product was purchased in the markets and towns near the city of Iquitos where we will stock up. The dehydration of Ginger or Kion (Zingiber Officinale) at the time of entering the Pilot Plant environments, proceeding with the flowchart: Raw material, fruit harvest, transport, selection/washing, disinfection, washing, cutting, drying, dried ginger. The experimental results were used in ANOVA, with a 1^3 factorial design and is represented by:?? = ??0 + ??1??1 + ??2??2 + ??3??3 + ??4??1 2 + ??5??1??2, with three factors: ??1 =Temperature (° C), ??2=Air speed (m/s), ??3=W_sample (g). Factor ??1has 2 levels (-1=45°C;1=55°C), factor ??2has 1 level (1=3m/s), Factor ??3has 1 level (1=0.21gr), with range of acceptance of (??2>85%) and the value P(P<0.05) or (Fcal>Ftable). The Humidity decreases with the increase in temperature at 45 ° C obtaining 9.64 % and at 55 ° C reducing to 5.22 %, both results are accepted from the microbiological point of view (there is no growth of fungi and yeasts) and guaranteeing nutritional quality. With the ANOVA statistical analysis, the humidity depends on the temperature factor without significantly reducing with the air velocity. With what has been described, it is concluded that the best temperature for dehydration of ginger or kion (Zingiber Officinale) is 55 °C because the moisture content substantially decreases.